Factors determining acceptance of coronavirus vaccine in diabetics at the endocrinology unit of Joseph Raseta Befelatanana Hospital - Razanamparany, Thierry; Lamaly, Emmanuel R.; Raherison, Rija E.; Randriamanantena, Tantely H. F.; Rakotohasina, Andriamparany; Andrianiaina, Miora M. A.; Rakotomalala, Andrianirina D. P.; Andrianasolo, Radonirina L. (International Journal of Research in Medical Sciences, 2025)
Background: Since the advent of the COVID-19 pandemic, diabetics have been categorized as being at risk of severe disease, and should benefit from vaccination to prevent the onset of severe disease and excess mortality. However, various studies reported limited participation of diabetic patients in vaccination. The aim of this study was to assess diabetic’s understanding and practices regarding vaccination against COVID-19 and the determining factors. Methods: This was a cross-sectional study conducted over a 6-month period. Diabetic outpatients and inpatients who were able to answer our questions and who had given informed consent were invited to participate. Patients unable to complete the survey were excluded from the study. Results: One hundred patients from the 110 diabetics included were retained, giving a participation rate of 90.9%. The median age of participants was 58.4 years (IQR: 19-85), with a sex ratio of 1.04. The positive determining factors significantly linked to participation in vaccination were the attainment of a university degree (p=0.04), confidence in the vaccine (p=0.02), and the presence of a personal history of infection or of being around COVID-19. Reasons for refusing vaccination included fear of the vaccine (88%) and of its adverse effects (80%). Conclusions: This study suggests the need to prioritize strategies focused on improving the level of information, education and knowledge of patients regarding the severity of coronavirus disease and the importance of vaccination.